Concepções manifestadas por professores de Matemática da escola pública sobre a utilização do computador na educação - Souza, Verônica Simão Esteves de (2006)
The aim of this research is to contribute to a rethinking of teacher education initiatives, be it in initial development, be it in continuous teaching development, focusing not only on implementation of Communication and Information Technologies and in the educational context, but on quality public education as a whole. In this sense we have sought to identify analyze conceptions of public school Mathematics teachers, who regularly use computers as a methodological resource. We also intend to: a) identify how teachers inserted technology in their practice: which technologies were applied, in what activities and guided by which objectives; b) identify which kind of continuous teaching development these teachers have to conduct such activities; c) identify conditions in which this working with technology occurs; d) identify difficulties faced by teachers and their expectations concerning implementation of IT in schools. In order to achieve such objectives questionnaires were applied with 24 Mathematics teachers in four public schools, among which two of which were selected for interviews. The research question that guided data collection is as follows: What are the conceptions expressed by Mathematics teachers concerning the use of computers in school? Data categorization and analysis were based on Teacher Formation and Mathematics Education references, particularly Communication and Information Technologies in Education, focusing on the concept of manifest conceptions as approached by Ponte (2002) and on the classification of Teacher conception types as approached by Thompson (1992), Ponte (1992) and Canavarro (1993). The results of the research show that, although teachers participate in training aimed at the use of computers as educational tool, few of them are able to use what they have learned in classroom, which in turn indicates that continuous teaching development is ineffective in this case. Moreover, they suggest that teachers use computers because they believe students need to be introduced to Information Society, although they conceive its use as a factor of motivation and facilitation, that is, a tool to do what was done before in a quicker and more modern way, which, in turn, steers away from the main objective of using Communication and Information Technologies at school.